2018
DOI: 10.1161/strokeaha.117.019060
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Prehospital Thrombolysis in Stroke Patients With Prestroke Dependency

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02358772.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…Previously disabled patients do not seem to be different from the others regarding the better outcome related to onset-to-treatment interval. In fact, a recent study by Nolte et al showed that prehospital start of IVT treatment on mobile stroke units, as compared with in-hospital care, may translate into better clinical outcomes in patients with pre-stroke dependency [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previously disabled patients do not seem to be different from the others regarding the better outcome related to onset-to-treatment interval. In fact, a recent study by Nolte et al showed that prehospital start of IVT treatment on mobile stroke units, as compared with in-hospital care, may translate into better clinical outcomes in patients with pre-stroke dependency [23].…”
Section: Discussionmentioning
confidence: 99%
“…106 Despite high mortality rates, observational studies of patients with pre-existing disability have indicated that IVT may prevent further functional deterioration and that treatment is more beneficial the earlier it is given. 107,108 Observational studies have not found evidence that pre-stroke disability is associated with an increased risk of ICH after thrombolytic treatment. 107,109,110 The recommendations for patients with multimorbidity, frailty or pre-stroke disability is based on small observational studies, corresponding to a very low quality of evidence.…”
Section: Expert Consensus Statementmentioning
confidence: 99%
“…With MSUs, earlier thrombolytic therapy—within the first, or golden, hour—after acute ischaemic stroke has been shown to be beneficial for patients with improved functional outcomes—for both patients who were independent and those who needed assistance in activities of daily living before their stroke (28, 3740). When compared to hospital-based thrombolysis in the first hour after acute stroke, MSUs have been shown to have comparable functional outcomes and mortality at 3 months (41).…”
Section: Introductionmentioning
confidence: 99%